2000
DOI: 10.1016/s0955-3959(00)00061-x
|View full text |Cite
|
Sign up to set email alerts
|

Citizens who inject drugs: the ‘Fitpack’ study

Abstract: Most injecting drug users have never been in drug treatment yet much research is done on samples with high treatment rates drawn from agency and peer recruited populations. This study accessed drug injectors with little or no prior drug treatment, described their characteristics, BBVI risk behaviours and feedback on services. Its results challenge some stereotypes about citizens who inject drugs. A sample of 511 'hidden' drug injectors, of whom only 28.7% had any specialist drug treatment agency contact, compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…In this situation, the potential risk of being infected with hepatitis C and/or hepatitis B is high among this group. Lenton and colleagues [22] also reported that pharmacy attendees in West Australia were more likely to re-use needles after someone else than IDU recruited from NSP. Strategies to improve clean injecting equipment access among non-NSP attendees are encouraged.…”
Section: Discussionmentioning
confidence: 98%
“…In this situation, the potential risk of being infected with hepatitis C and/or hepatitis B is high among this group. Lenton and colleagues [22] also reported that pharmacy attendees in West Australia were more likely to re-use needles after someone else than IDU recruited from NSP. Strategies to improve clean injecting equipment access among non-NSP attendees are encouraged.…”
Section: Discussionmentioning
confidence: 98%
“…The major limitation of this study is that data regarding the number of needles and syringes dispensed from, and returned to, pharmacies were not obtainable. This is notable when considering the findings of Lenton et al [15] that IDUs who purchase needles from pharmacies constitute a different group of IDUs. However, NSP data and interview responses suggest that pharmacies constitute a minor source of needles within the Geelong region.…”
Section: Limitationsmentioning
confidence: 96%
“…One, and by no means the only, example of this in WA was research conducted in 1995 with 511 drug injectors who purchased their needles in pharmacy. This showed that many had shared other injecting equipment such as spoons and filters and that the cost of needles and the numbers sold per pack lead to needle sharing and reuse by some injectors [11]. These findings were conveyed to both needle kit manufacturers (organizational level) and health bureaucrats (State level) responsible for prevention of blood-borne viral infections among injecting drug users.…”
Section: Using the Framework: A Practical Examplementioning
confidence: 97%
“…Largely due to the early adoption of HIV prevention strategies among injecting drug users, WA is thought to have one of the lowest rates of HIV infection among drug injectors in the developed world, with only approximately 1 -2% of injectors infected [11,12]. This example ideally shows how the prevention framework presented here can help identify what prevention activities could be undertaken to identify various mechanisms of action at various community levels to help prevent blood-borne viruses among people who inject drugs.…”
Section: Using the Framework: A Practical Examplementioning
confidence: 99%